Pengaruh Work Environment Dan Self Efficacy Terhadap Work Engagement Yang Dimediasi Oleh Organizational Trust - Anam, Saripul; Anggarani W.P.T, Ari (CV. Lafadz Jaya, 2023)
The purpose of this study was to explore the effect of work environment and self efficacy on work engagement mediated by organizational trust. This research was conducted on employees of PT. Keramindo Megah Pertiwi (KMP). The sampling technique used in this study was a non-probability sampling method with a purposive sampling technique of 151 respondents. The results of this study prove that the work environment has an effect on work engagement, self-efficacy has no effect on work engagement, organizational trust has an effect on work engagement, work environment has had an effect on organizational trust, self-efficacy has had an effect on organizational trsut. In addition, the results of mediation in research prove that organizational trust does not mediate the relationship between work environment with work engagement, organizational trust mediates the relationship between self-efficacy with work engagement.